2004
DOI: 10.1080/0960312042000209516
|View full text |Cite
|
Sign up to set email alerts
|

Association between nutritional status and arsenicosis due to chronic arsenic exposure in Bangladesh

Abstract: The role of nutritional factors in arsenic metabolism and toxicity is not clear. Provision of certain low protein diets resulted in decreased excretion of DMA and increased tissue retention of arsenic in experimental studies. This paper reports a prevalence comparison study conducted in Bangladesh to assess the nutritional status among the chronic arsenic exposed and unexposed population. 138 exposed individuals diagnosed as arsenicosis patients were selected from three known arsenic endemic villages of Bangla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 34 publications
2
43
0
Order By: Relevance
“…An epidemiological study conducted in West Bengal, India showed male gender and malnutrition correlated with increased prevalence of skin manifestations in arsenic exposed population [20]. In a recent study, an association between nutritional status and chronic exposure to arsenic has been reported among Bangladeshi patients [21].…”
Section: Number Of Patients With Clinical Symptomsmentioning
confidence: 99%
“…An epidemiological study conducted in West Bengal, India showed male gender and malnutrition correlated with increased prevalence of skin manifestations in arsenic exposed population [20]. In a recent study, an association between nutritional status and chronic exposure to arsenic has been reported among Bangladeshi patients [21].…”
Section: Number Of Patients With Clinical Symptomsmentioning
confidence: 99%
“…The studies were reported that low socio-economic status and poor nutritional status of arsenicosis sufferers people in Taiwan and Chile [16], [17], [19], [41]. Lower BMI was reported among the arsenicosis patients compared to the unexposed population in a previous study in Bangladesh [40]. However, a study from Atacameño in northern Chile reported no evidence of malnutrition among individuals with arsenic induced skin lesions [42].…”
Section: G Association Between Bmi and Arsenic Concentration In Urinementioning
confidence: 90%
“…Among the obesity 50.00%, 33.33% and 16.67% of the sample respondents contained more than 200 to 500, more than 500 to 1000 and more than 1000 μg/g arsenic in urine, respectively. In a recent study, an association between nutritional status and chronic exposure to arsenic has been reported among Bangladeshi patients [40]. Number of sample respondents in the parentheses.…”
Section: G Association Between Bmi and Arsenic Concentration In Urinementioning
confidence: 99%
See 1 more Smart Citation
“…This is an expensive procedure but its use is at last beginning to assist with compiling a list of registered sufferers, for whom some remediation may be possible through better nutrition and a switch to the consumption of safe water. The irony here is that the best treatment for arsenic would be to cure poverty since it is people in the lowest income quartile and the malnourished who are most susceptible to arsenicosis and to the accompanying socio-economic fallout (WHO, 2000;Milton et al, 2004;Hadi and Parveen, 2004).…”
Section: Expert Knowledgesmentioning
confidence: 99%